Konseling Multi Budaya dalam Mengatasi Perbedaan Gender pada Film “Keluarga Cemara” - Naila Faizah; Arum Arum (Da'wah Faculty of UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2025)
Gender differences in the family are often a source of problems when roles and responsibilities are not understood or agreed upon fairly. The purpose of this study is to explore the multicultural counseling that exists within the Cypress family in addressing gender differences. This study employs qualitative description research, grounded in library research methods, as a means of assessing and offering ideas in cross-cultural counseling and field research to identify cultural issues. The result of this study is that there is no gender gap; men and women have the same tasks in this world. In the film